Facilitation for Undergraduate College Students to Learn Java Language Using E-Learning Model - Alfarsi, Ghaliya; Tawafak, Ragad; Malik, Sohail; Khudayer, Baidaa Hamza (International journal of interactive mobile technologies, 2022)
The use of modern programming in Java has become widely used in the e-learning model to help the student learn in the right place and time. Students have difficulty learning Java and are time-consuming without the benefit of understanding the material. This study presents how to build an electronic application to facilitate learning programming in modern languages. In order to confirm the effectiveness of the application, a questionnaire was developed on the need for an educational application that helps facilitate the process of learning Java and the need for diversity in the methods of educational methods. The study of this questionnaire appeared from the need for this educational electronic application. After applying the application to the same sample of students, they expressed their satisfaction and satisfaction with this application, and the impact of this use of this application in raising the educational level of the student in this subject The results show and reflect the good interest from students of this application.